A retrospective review of the common childhood illnesses and the indications for antibiotic prescription at community hospital in Malawi - Lubanga, Adriano Focus; Khuluza, Chana; Muhyuddin, Jamillah; Simfukwe, Reuben; Kaphesi, Frank; Yeum, Yeo Hwan; Yoon, Joshua J.; Kim, Changwoo; Kim, Seunghyun; Kim, Si Yeon; Lee, Ji An; Park, Jooheon; et al. (Frontiers in Antibiotics, 2024)
Background: Childhood remains a vulnerable period and a key determiner for adult health.Various illnesses experienced by children in their early years determine future performance and contribution to society. Acute and chronic infectious diseases, undernutrition, and early childhood non-communicable diseases have greatly been linked to intellectual disability, poor childhood development, increased morbidity, and household and healthcare economic costs. In most developing countries, infections contribute to a larger burden of disease. Despite this being the case, most developing countries have a limited range of diagnostic capacity and access to a wide range spectrum of WHO Access, Watch and Reserve antibiotics. This leads to overuse and misuse of the available antibiotics and a wide range spread of resistance strains. In this study, we evaluated common childhood presentations and indications for antibiotic prescriptions at a community hospital in Malawi.Objective: This study analyzed common childhood Clinical Presentations and antibiotic prescription patterns at the pediatric outpatient department (OPD) at St. Gabriel Community Mission Hospital in Malawi.A retrospective search of all outpatient routinely corrected data from St. Gabriel Community Mission Hospital between January to December 2022 was carried out. Manual screening was done on all appropriate routines under 14 medical records, and prespecified variables were extracted. Data collected consisted of total OPD patient number, age, sex, diagnosis and prescription.Results: A total of 2711 children under 15 years of age were included, with 53.9% being males.The majority of them were below the age of 5 (59.5%). 30 % of the cases seen in the department were attributable to respiratory presentation, representing the majority of the cases seen. Sepsis